The Benefit of a Visually Guided Beamformer in a Dynamic Speech Task. - Best, Virginia; Roverud, Elin; Streeter, Timothy; Mason, Christine R.; Kidd Jr., Gerald (Trends in Hearing)
The aim of this study was to evaluate the performance of a visually guided hearing aid (VGHA) under conditions designed to capture some aspects of ‘‘real-world’’ communication settings. The VGHA uses eye gaze to steer the acoustic look direction of a highly directional beamforming microphone array. Although the VGHA has been shown to enhance speech intelligibility for fixed-location, frontal targets, it is currently not known whether these benefits persist in the face of frequent changes in location of the target talker that are typical of conversational turn-taking. Participants were 14 young adults, 7 with normal hearing and 7 with bilateral sensorineural hearing impairment. Target stimuli were sequences of 12 question–answer pairs that were embedded in a mixture of competing conversations. The participant’s task was to respond via a key press after each answer indicating whether it was correct or not. Spatialization of the stimuli and microphone array processing were done offline using recorded impulse responses, before presentation over headphones. The look direction of the array was steered according to the eye movements of the participant as they followed a visual cue presented on a widescreen monitor. Performance was compared for a ‘‘dynamic’’ condition in which the target stimulus moved between three locations, and a ‘‘fixed’’ condition with a single target location. The benefits of the VGHA over natural binaural listening observed in the fixed condition were reduced in the dynamic condition, largely because visual fixation was less accurate.